(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Dyslipidemia has been noted to play an integral role in the pathogenesis and progression of micro and macrovascular complications in Diabetes Mellitus (DM) patients. Lipid profile is the indicators of dyslipidemia. Objectives: To evaluate the prevalence and pattern of dyslipidemia in type 2 DM patients. Materials and Methods: This cross sectional study was conducted at Armed Forces Institute of Pathology (AFIP) from November 2014 to October 2015. The study included 300 type 2 diabetic patients belonging to the age group 30-59 years. Personal data and history of co-existing medical conditions were collected by data collection sheet and analyzed. Results: Among 300 study subjects with type 2 DM the prevalence of dyslipidemia was 94% among them 19% had single dyslipidemia and 75% had multiple dyslipidemia. In this study, high level of total cholesterol (TC), triglycerides(TG) and Low Density Lipoprotein-Cholesterol (LDL-C) were found in 47.3%, 76.7% and 41.3% patients respectively. High Density Lipoprotein- Cholesterol (HDL-C) levels were found to be low in 60% patients. Conclusion: The study revealed that dyslipidemia is very common in type 2 diabetic patients and the most common abnormality observed was increased serum TG level followed by decreased HDL-C level. So, patients with type 2 DM should be followed up with serum lipid profile regularly. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 177-179